Repeal of the Pennsylvania motorcycle helmet law: reflections on the ethical and political dynamics of public health reform - Cherry Robert A (BMC, 2010)
Abstract Background In June of 2003 the Commonwealth of Pennsylvania passed S. 259 which repealed the state's 35-year old motorcycle helmet safety law. Motorcycle helmets are now only required for riders who are under the age of 21 and for those who are 21 years or older who have had a motorcycle operator's license for less than two years, or who have not completed an approved motorcycle safety course. Discussion Prior to the repeal, and in the years that have followed, there has been intense debate and controversy regarding Pennsylvania's decision to repeal the law that required universal and mandatory use of motorcycle helmets for all riders. Proponents of the helmet repeal have argued in favor of individual rights and freedom, whereas advocates for mandatory helmet laws have voiced concerns over public health and safety based on available data. Summary This commentary will discuss the policy-making process that led to Pennsylvania's repeal of the motorcycle helmet safety law from an ethical, political, and economic perspective.